Phase transition and nanomechanical properties of refractory high-entropy alloy thin films: effects of co-sputtering Mo and W on a TiZrHfNbTa system. Issue 20 (28th April 2022) - Cheng, Changjun; Zhang, Xiaofu; Haché, Michel J. R.; Zou, Yu
Abstract : Based on magnetron co-sputtering, Mo/W additions result in the phase transition of TiZrHfNbTa high-entropy alloy from nanocrystalline to amorphous structures, leading to an obvious increase in hardness with a slight increase in the elastic modulus. Abstract : Refractory high-entropy alloys (RHEAs) that consist of multiple principal refractory elements have attracted significant attention due to their many interesting and useful properties for structural applications. However, so far, a vast majority of reports on RHEAs focused on a few well-known compositions such as NbMoTaW, NbMoTaWV, and TiZrHfNbTa. The discovery of new RHEAs with enhanced mechanical properties has been highly desirable. Here we produce two new RHEA thin films – TiZrHfNbTaMo and TiZrHfNbTaW, by co-sputtering Mo or W on a previously studied TiZrHfNbTa RHEA system. The TiZrHfNbTaMo and TiZrHfNbTaW thin films exhibit an amorphous state, while the TiZrHfNbTa one shows a nanocrystalline structure. Using the nanoindentation method, we show that the addition of Mo or W in the TiZrHfNbTa during the co-sputtering process increases the hardness while resulting in comparable elastic moduli. Through the strain rate sensitivity tests of the thin films, we obtain their activation volumes and discuss their deformation mechanisms in the nanoindentation tests.